Low-Intensity Focused Ultrasound Stimulation Ameliorates Working Memory Dysfunctions in Vascular Dementia Rats via Improving Neuronal Environment - Wang, Faqi; Wang, Qian; Wang, Ling; Ren, Jing; Song, Xizi; Tian, Yutao; Zheng, Chenguang; Yang, Jiajia; Ming, Dong (Frontiers in Aging Neuroscience, 2022)
Working memory impairment is one of the remarkable cognitive dysfunctions induced by vascular dementia (VD), and it is necessary to explore an effective treatment. Recently, low-intensity focused ultrasound stimulation (LIFUS) has been found notable neuroprotective effects on some neurological diseases, including VD. However, whether it could ameliorate VD-induced working memory impairment was still not been clarified. The purpose of this study was to address this issue and the underlying mechanism. We established VD rat model using the bilateral common carotid artery occlusion (BCCAO) and applied the LIFUS (center frequency = 0.5 MHz; Ispta = 500 mW/cm2, 10 mins/day) to bilateral medial prefrontal cortex (mPFC) for 2 weeks since 2 weeks after the surgery. The main results showed that the LIFUS could significantly improve the performance of VD rats in the specific working memory tasks (delayed nonmatch-to-sample task and step-down task), which might be associated with the improved synaptic function. We also found the improvement in the cerebral blood flow (CBF) and reduced neuroinflammation in mPFC after LIFUS treatment indicated by the inhibition of Toll-like receptor (TLR4)/nuclear factor kappa B (NF-κB) pathway and the decrease of proinflammatory cytokines. The amelioration of CBF and neuroinflammation may promote the living environment of the neurons in VD which then contribute to the survival of neurons and the improvement in synaptic function. Taken together, our findings indicate that LIFUS targeted mPFC can effectively ameliorate reward-based spatial working memory and fear working memory dysfunctions induced by VD via restoring the living environment, survivability, and synaptic functions of the neurons in mPFC of VD rats. This study adds to the evidence that LIFUS could become a promising and non-invasive treatment strategy for the clinical treatment of central nervous system diseases related to cognitive impairments in the future.